Physiological responses of Coffea arabica cultivars in association with arbuscular mycorrhizal fungi - de Sousa Cruz, Rafaele; Vieira Araújo, Fausto Henrique; Cabral França, André; Tadin Sardinha, Levy; Miranda Machado, Caroline Maira (Coffee Science - ISSN 1984-3909, 2020)
The inoculation of coffee plants with arbuscular mycorrhizal fungi (AMF) may influence some of its physiological parameters, promoting benefits in the growth of newly planted coffee. The objective of this work was to evaluate the physiological responses of different cultivars of Coffea arabica inoculated with arbuscular mycorrhizal fungi. The experiment was conducted in a vegetation house in Diamantina, state Minas Gerais. The design was in randomized blocks, in a 3 x 4 factorial scheme, with four replications. The factors were composed of coffee seedlings of Rubi (MG 1192), Mundo Novo (IAC 379-19) and Catuaí Vermelho (IAC 144) cultivars, inoculated or not with FMA Rhizophagus clarus, Acaulospora colombiana and Mix composed by R. clarus and A. colombiana. At 150 days after transplantation, physiological characteristics such as photosynthetic rate, internal carbon concentration, stomatal conductance, transpiration rate, water use efficiency, internal carbon / atmospheric carbon ratio and percentage of mycorrhizal colonization were evaluated. AMF inoculation affected positively the physiology of coffee plants, increasing photosynthetic rate (A), stomatal conductance (Gs), transpiration, carbon consumed (ΔCO2), water use efficiency (EUA) and percentage of mycorrhizal colonization (%), as well as reducing the internal carbon concentration (Ci) for all combinations of AMF cultivars and species. The cultivar Rubi, when inoculated with R. clarus or Mix, obtained a higher percentage of colonization. The physiological activity of coffee plants is altered by symbiotic association, and their responses varied between AMF species and cultivars. Key words: Coffee; Mycorrhiza; Photosynthesis; Plant growth.